Notary Public Authority in Marital/Partnership Relations - Kovaček Stanić, Gordana (Zbornik radova Pravnog fakulteta u Novom Sadu, 2012)
In Serbian legislation notary public profession is introduced recently, inacting the Act on Public Notary 2011. Notary public has existed in Serbia before World War II, but after the War this profession ceased to exist, as it was not regulated by law. In this article author discusses issue of the public notary authority in marital/partnership relations. Public notary has authority in property relations and support. Regarding property relations, according to the Act on Notary Public, agreement on division of the community of property might be concluded in specific notarial form. In addition, nuptial agreements (pre nuptial or antenuptial) might be concluded in specific notarial form. The same is applied to the partners agreements if partners live in heterosexual nonmarital cohabitation, regulated by Family Act. Regarding support, public notary has authority to issue agreements on support. It is important to stress that in Serbian family law waiving the right to support has no legal bearing.